The governance of quality and safety in Tanzania's informal milk markets - Blackmore, E.; Guarín, A.; Kinyua, Charity; Vorley, W.; Grace, Delia; Alonso, Silvia (Frontiers Media, 2022)
Despite significant economic and social transformation in Tanzania, 95% of the milk produced in Tanzania is marketed informally. Most of this is commercialized raw (unpasteurized) and distributed and sold through informal traders and vendors to low-income consumers, making it an important source of nutrition and livelihoods. While Tanzania's official dairy policy promotes pasteurization and formal industry, in practice the regulatory environment is relatively permissive of informal raw milk trade. We draw on original data from a survey with over 200 informal market actors, and insights from key informant interviews, to examine the context, perceptions and practices that affect quality and safety in the informal milk market in Tanzania. Our insights contribute to the potential for a more realistic and effective engagement with the informal sector, in Tanzania and beyond. Our results show that all informal market actors are concerned with milk quality and safety and take measures to mitigate risk. Loyalty and repeated interactions between buyers and sellers contribute to ensuring milk quality and safety in the absence of formal mechanisms such as testing. Despite this there is room for improvement. Informal actors expressed interest in training and finance to upgrade their premises and equipment and would also like to see improved communication with policymakers. Any future policy interventions should build on the indigenous practices being used by informal actors that already contribute to risk management. Efforts to better understand the informal sector and address the broader challenge of the lack of voice and representation of the informal sector in policy making in Tanzania are needed.